Excited states from range-separated density-functional perturbation theory - Rebolini, Elisa; Toulouse, Julien; Teale, Andrew M.; Helgaker, Trygve; Savin, Andreas (Taylor and Francis, 2015)
We explore the possibility of calculating electronic excited states by using perturbation theory along a range-separated adiabatic connection. Starting from the energies of a partially interacting Hamiltonian, a first-order correction is defined with two variants of perturbation theory: a straightforward perturbation theory, and an extension of the Görling-Levy one that has the advantage of keeping the ground-state density constant at each order in the perturbation. Only the first, simpler, variant is tested here on the helium and beryllium atoms and on the hydrogen molecule. The first-order correction within this perturbation theory improves significantly the total ground- and excited-state energies of the different systems. However, the excitation energies mostly deteriorate with respect to the zeroth-order ones, which may be explained by the fact that the ionization energy is no longer correct for all interaction strengths. The second (Görling-Levy) variant of the perturbation theory should improve these results but has not been tested yet along the range-separated adiabatic connection.